Ill weeds grow apace - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
This useful website with databases of the International Survey of Herbicide Resistant Weeds (ISHRW) is a collaborative effort between weed scientists in over 80 countries, who maintain scientific accuracy in the reporting of herbicide resistant...